The Influence Of Social Media On The Resilience Of Rural Communities During The Covid-19 Pandemic - Widodo, Bambang Sigit; Budiati, Atik Catur; Octavianto, Dwi Angga; Lestari, Alif Putra; Silva, Pedro M (The Journal of Society and Media, 2021)
Indonesia is currently facing a new wave of COVID-19 transmission with the number of transmissions rising significantly. The community compliance factor is one of the important things in the spread of the Covid-19 rate. There needs to be intensive warning efforts, including campaigns through social media. This study aims to determine the effect of social media on the level of resilience in rural communities during the covid-19 pandemic. The research sample purposively amounted to 213 people from two research locations, namely Sambong Dukuh Village, Jombang Regency and Wonocoyo Village, Trenggalek Regency, Indonesia. The results showed that the p value = 0.001 < 0.05, which means that social media has a significant effect on the level of community resilience in dealing with the covid-19 pandemic. Furthermore, based on the R2 value, the result is 0.421, which means that social media has an influence on the community's resilience level of 42.1%, and the rest are other influences not examined in this study. Based on the results of the t test, it was found that the p value = 0.467 > 0.05, so it can be said that there is no significant difference between the level of resilience in the community in the two villages, even though the average value of Wonocoyo village is 77,393 better than Sambong Dukuh village of 77.00 , but the difference was not statistically significant. The researcher recommends the importance of further research on resilience based on regional characteristics.